1994
DOI: 10.1530/eje.0.1300080
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bromocriptine and SMS 201-995 on growth of human somatotrophic and non-functioning pituitary adenoma cells in vitro

Abstract: The effect of the dopamine agonist bromocriptine and the somatostatin analog SMS 201-995 on growth of 12 human somatotrophic and 13 non-functioning adenoma cell cultures was investigated. When adenoma cells were maintained in medium supplemented with 5% fetal calf serum, cell counts of 10 of 12 somatotrophic cultures increased to 145 +/- 6 and 171 +/- 9% (mean +/- SD) and in 12 of 13 non-functioning cell cultures up to 125 +/- 12 and 217 +/- 15% after 3 days of incubation. In most cases bromocriptine and SMS 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 0 publications
4
20
0
Order By: Relevance
“…However, the effects of the DA agonist bromocriptine on reducing NFPA size has been disappointing, as most studies have shown only modest size reduction in a minority of treated tumors (12,14,17,21,25). Therefore, bromocriptine therapy has not been advocated on a routine basis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the effects of the DA agonist bromocriptine on reducing NFPA size has been disappointing, as most studies have shown only modest size reduction in a minority of treated tumors (12,14,17,21,25). Therefore, bromocriptine therapy has not been advocated on a routine basis.…”
Section: Discussionmentioning
confidence: 99%
“…Radiotherapy is the only modality shown to be effective in the prevention of residual tumor growth (7)(8)(9). The use of dopamine (DA) agonists has been previously explored as a treatment alternative for NFPA (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). Greenman and co-workers have shown that postoperative DA treatment resulted in a decrease or stabilization of tumor mass in 90% of patients in contrast to 2 and 5 years re-growth rates of 30 and 70% in untreated patients respectively (26).…”
Section: Introductionmentioning
confidence: 99%
“…In healthy subjects, bromocriptine decreases the plasma prolactin level, but not the gonadotropin level (16). Sufficient effects of this drug were reported in some patients with growth hormone- ( 14,17,18) or corticotropin-(19) producing pituitary adenoma. In patients with thyrotropin-producing adenomabromocriptine is generally not effective (20).…”
Section: Discussionmentioning
confidence: 99%
“…The bioactivity of bromocriptine increases when administered alongside octreotide (17). In vitro studies highlighted that both bromocriptine and octreotide at high doses are able to inhibit cell growth from human somatotroph adenomas (18). A dose of 1 nmol/l bromocriptine decreased cell growth in 40% of somatotroph cell cultures, whereas 10 mmol/l decreased cell counts in all somatotrophs and in 92% of non-functioning adenoma cultures.…”
Section: Gh-secreting Tumoursmentioning
confidence: 99%
“…The use of a combined somatostatin analogue and dopamine agonist treatment schedule seems to be of particular interest in growth hormone (GH)-secreting adenomas that are known to be potentially responsive to both classes of compounds (16)(17)(18)(19)(20)(21)(22)(23)(24)(25). More recently, nonfunctioning pituitary adenomas were shown to be sensitive to a combined treatment, whereas the response rate to somatostatin analogues or dopamine agonists alone is limited.…”
Section: Introductionmentioning
confidence: 99%